Coronary artery disease in patients after orthotopic heart transplantation treated with percutaneous coronary intervention – a single centre experience - Sobieszczańska-Małek, Małgorzata; Zieliński, Tomasz; Karcz, Maciej; Piotrowska, Małgorzata; Kalińczuk, Łukasz; Komuda, Krzysztof; Bekta, Paweł; Witkowski, Adam; Rużyłło, Witold; Korewicki, Jerzy (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2010)
Background : Some patients after orthotopic heart transplantation (OHT) develop coronary focal lesions and may need interventional therapy. Aim : To determine the frequency and time course of narrowing of epicardial coronary arteries in transplanted hearts, potential risk factors and results of percutaneous coronary interventions. Methods and results : Demographic and coronary angiography data of 265 patients after OHT, mean age 53.0 ±14.6, were analysed. Significant focal narrowing of the coronary artery was diagnosed when there was a decrease of 50% or more of the lumen of the coronary artery. Mean time from OHT to the end of observation was 6.2 ±4.5 (range 0.5-23) years. Thirty-six (14%) patients after OHT had significant focal changes in coronary arteries. In 16 patients the degree of stenosis, lesion, location or calibre of the vessel was not suitable for interventional therapy. Twenty (55%; 18 men) patients underwent coronary intervention. Mean age of patients during coronary intervention was 53.5 ±9.8 years and of those without intervention at the end of observation was 52.5 ±14.9 years (NS). In patients with intervention mean time from OHT to intervention was 7.0 ±4.6 years. In patients with coronary intervention mean time from OHT to the end of observation was 10.8 ±6.5 years and in patients without intervention 5.8 ±4.1 (p < 0.001). Analysis of Kaplan-Meier curves showed that probability of coronary stenosis-free survival diminishes rapidly after 5 years following OHT. Patients who required coronary intervention had significantly higher hsCRP as compared to those without intervention (0.720 vs. 0.044, p = 0.025). There were no statistical differences between the two groups in cholesterol level, BMI or incidence of diabetes, number of acute cellular episodes or Quilty effect. Conclusions : Significant focal coronary stenoses are found mainly more than 5 years post heart transplantation. Most patients can be treated safely and effectively with percutaneous coronary intervention with contrast-induced nephropathy prophylaxis. Risk factors of coronary vasculopathy post OHT require further investigations.